The Paracoccidioides brasiliensis gp70 antigen is encoded by a putative member of the flavoproteins monooxygenase family - Maricato, Juliana T.; Batista, Wagner L.; Kioshima, Erika S.; Feitosa, Luciano S.; Novaes e Brito, Ronni R.; Goldman, Gustavo H.; Mariano, Mario [UNESP]; Puccia, Rosana; Lopes, Jose D. (Academic Press Inc. Elsevier B.V., 2010)
Glycoprotein gp70 is an important intracellular antigen from Paracoccidioides brasillensis that elicits both humoral and cellular immune responses. Herein, the PbGP70 gene cloning from isolate Pb18 using internal peptide sequence information is reported. The deduced protein sequence bears two N-glycosylation sites, antigenic sites and two mouse T-cell epitopes. Anti-recombinant gp70 (rPbgp70) polyclonal antibodies reacted with a 70-kDa component in total cell extract of A brasiliensis, while MAbC5F11 and paracoccidioiclomycosis patients' sera recognized rPbgp70. Confocal microscopy with anti-rPbgp70 and MAbC5F11 showed intense staining and cytoplasmatic co-localization. The protein sequence belongs to the flavoprotein monooxygenase family which groups important anti-oxidative bioactive compounds. We found increased PbGP70 transcript accumulation under oxidative stress induced by H(2)O(2), during fungal growth and in macrophage phagocyted/bound yeasts. Therefore, gp70 might play a dual role in P. brasiliensis by both eliciting immune cellular and humoral responses in the host and protecting the fungus from oxidative stress generated by phagocytic cells. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: Paracoccidioides brasiliensis; Antigen; Flavoprotein; Oxidative stress